Islabodan - Tarobal, Juan Carlo Balasbas 1987-; Jamon, Roehl L.; University of the Philippines Diliman. College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2017)
"Islabodan is a story about a lone, apathetic plastic bottle collector, Caloy, who gets caught in the middle of two warring gangs of plastic bottle collectors like him which changes his life forever. The anarchist school of thought infused with libertarian and communist disciplines are the key ingredients of the film as this is the vision of the filmmaker for a better world. Alongside a pinch of existentialist thought for the thorough brewing of what is to come as the ultimate realization and clarity of a goal which is to eliminate the elitist way of running things. However, should the goal be achieved, do we stop? Or should the goal be not achieved, do we also stop? We are left with a challenge to carry on and push onward with hope in our hands."
Vita.
Thesis (A.B. Film)--University of the Philippines Diliman
Includes bibliographical references.
Keywords: Short films -- Philippines